Survivability reconfigurable techniques in optical network. Issue 5 (4th July 2019) - Sairam, K. V. S. S. S. S.; Singh, Chandra; Sai Vamsi, P; Sreekantha, D K; Annapurna, Kanduri; Rao, Kanduri Sarveswara
Abstract: Survivability plays a vital role against to stop the failure. It results the demand distribution in Optical Networks through different communication services like data voice and video by using huge bandwidth. In this paper Techniques for Survivability of Optical Networks through Network Configuration is presented Hence the centralized and non-centralized demand distribution in Optical Networks through different communication services like data voice and video by using huge bandwidth. In this paper Techniques for Survivability of Optical Networks through Network Configuration is presented. Hence these techniques are evaluated by using the parameters such as Traffic Characterization (TC), Traffic Protection and Restoration (TPR), Network Path Configuration and Network Integration w.r.t. Physical Layer(PL) and Logical Layer(LL) problem formulation(s) are discussed. Hence the survivability of fiber Optic Network play a vital role for NXN connectivity. Reconfigurable implies Optical Network Services Utilization Factor(ONSUF) is estimated through the local and global connectivity scenario.